2013
DOI: 10.1111/coa.12153
|View full text |Cite
|
Sign up to set email alerts
|

An audit of the nature and impact of clinical coding subjectivity variability and error in otolaryngology

Abstract: Otolaryngology coding is complex and susceptible to subjectivity, variability and error. Coding variability can be improved, but not eliminated through regular education supported by an audit programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 7 publications
3
28
0
Order By: Relevance
“…A coder, however, would look through the clinical records and look for the condition being documented by the clinical team. We have previously shown that the particular subset of diagnoses where the diagnosis can be inferred from numerical results are subject to significant subjectivity, variability and error as clinical coders cannot infer a diagnosis from numbers alone . It is possible to produce local and national coding policies to enable the coders to equate post‐treatment blood calcium levels with the diagnosis of Post‐procedural Hypoparathyroidism (E892).…”
Section: Discussionmentioning
confidence: 99%
“…A coder, however, would look through the clinical records and look for the condition being documented by the clinical team. We have previously shown that the particular subset of diagnoses where the diagnosis can be inferred from numerical results are subject to significant subjectivity, variability and error as clinical coders cannot infer a diagnosis from numbers alone . It is possible to produce local and national coding policies to enable the coders to equate post‐treatment blood calcium levels with the diagnosis of Post‐procedural Hypoparathyroidism (E892).…”
Section: Discussionmentioning
confidence: 99%
“…Haliasos et al [3] found at least one coding error in 18.4% of neurosurgical cases, and HRG changes in 10.4%, with a loss of £111 per patient episode. In Nouraei et al [13], their ENT coding audit led to at least one change of coding in 44% of cases, and to HRG changes in 16%, with an income variance of £109.46 per patient. In Naran et al [14], their audit led to at least one change of coding in 77% patients, and to HRG code changes in 54% patients, with an estimated £114 in lost revenue per patient.…”
Section: Comparison With Literaturementioning
confidence: 99%
“…Otolaryngology (ENT) is comparable to HPB in terms of the complexity and subtle differences between the procedures performed. Studies on coding accuracy in ENT have reported similar high levels of coding error with nearly a quarter of cases having coding inaccuracies with over half of these resulting in reduced tariffs . Results from these data suggest that it may be beneficial for coding departments to be specialty based and each department is assigned its own coder.…”
Section: Discussionmentioning
confidence: 83%